The medium to long term sequelae of endoscopic sphincterotomy in the management of common duct stones in HUSM (1992-1998) - Salekan , Khairuzi (2001)
Recent development of new cannulation instruments and techniques, improvement in the lithotripsy methods and the advent of laparoscopic surgery have changed the management of common duct stones. Previously surgical intervention was the mainstay of treatment, but now most can be successfully treated endoscopically. Endoscopic Retrogradecholangiopancreatography (ERCP) and Endoscopic Sphincterotomy (EST) is accepted as the gold standard for the management of common duct stones. There are many reports of early results of EST, however few reviews regarding the medium to long term sequelae of EST for the treatment of common duct stones. The local data about this subject is very scanty. Hence forth a study conducted to include the demography, success rate and medium to long term sequelae of EST in patients with common duct stones. This is a retrospective descriptive study done on 224 patients with common duct stones who underwent EST in Endoscopy Unit of Hospital Universiti Sains Malaysia from 1992 to 1998. The study showed that majority of the patients was Malays with female preponderance. The incidence occurred in the younger age group compared with other reported series. However majority of them were lost from follow up as they were being referred from other hospitals. Our study showed a success rate of 90°/o which are comparable with other series. In our study 53.5 °/o were symptom free, while the remainder ( 46.5 o/o) were noted to have some digestive complaints during the follow-up period. Out of 20 patients who were symptomatic during follow up after EST, biliary consequences occurred in 15 ( 75 % ) of patients and non biliary consequences occurred in 2 (10 %) of patients and non specific diagnosis in 3 ( 15 °/o ) of patients. 9 patients ( 45 o/o ) were diagnosed to have choledocholithiasis with or without associated strictures, ascending cholangitis or cholelithiasis. 2 patients had cholelithiasis. Another 1 patient had ascending cholangitis, biliary chirrosis, cholecystitis with cholelithiasis, oriental cholangitis, gastritis and sigmoid colon carcinoma, respectively.